A Tale of Two Markets: Unequal Access to Private Property in a South African City. (20th June 2019) - Marais, Lochner; Awuzie, Bankole; Cloete, Jan; Napier, Mark; Greyling, Erica
Abstract: In line with international trends, South Africa's post‐apartheid government has embarked on a housing policy that emphasises asset building. Homeownership has become a dominant policy for assisting the historically disadvantaged Black population. This paper looks at two property markets in Mangaung, a metropolitan municipality that includes Bloemfontein. We analysed property activity on 2, 545 residential stands in former Black and former White areas in Mangaung since 1990. Our findings show two distinct markets. The formal property market in former Black areas shows a low number of transactions, low value and slow turnover. In the former White areas, a housing investment made between 1990 and 2016 would have yielded an annual return of 14 per cent, but in the former Black areas only 7 per cent. This poor return makes it difficult for homeowners in former Black areas to use housing for asset building. Abstract : Homeownership has become a dominant policy for assisting the historically disadvantaged Black population in South Africa. This article looks at property activity in former Black and former White areas in Mangaung since 1990. The findings show two distinct markets, with annual return in former White areas being substantially higher, and with the difficulty for homeowners in former Black areas to use housing for asset building.